Primary and Secondary Diagnoses of Gambling Disorder and Psychiatric Comorbidity in the Swedish Health Care System—A Nationwide Register Study - Håkansson, Anders; Karlsson, Anna; Widinghoff, Carolina (Frontiers in Psychiatry, 2018)
Background Psychiatric comorbidity is common in gambling disorder, a condition with low rates of treatment seeking. There is a paucity of documented nationwide data on gambling disorder and its co-occurring psychiatric comorbidities in the health care system. Methods This is a nationwide register-based study of all patients aged above 18 years who were diagnosed with gambling disorder (corresponding to pathological gambling, code F63.0, in the ICD-10) in Swedish specialized out-patient health care or in-patient care, from 2005 through 2016. All psychiatric disorders co-occurring with the diagnoses were recorded, along with age, gender and the type of medical specialty. Results A total of 2,099 patients were included (1,784 in out-patient care and 629 patients in in-patient care), among whom 77 percent were men. Treatment uptake during the study period increased significantly in out-patient care, with an increasing uptake of younger individuals, whereas in-patient treatment uptake remained stable. A co-occurring psychiatric diagnosis was registered in 73 percent of patients, more commonly in females (77 vs 71 percent, p<0.01). Several diagnostic subgroups were more common in women, with anxiety and affective disorders being the most common subgroups. Prevalence of substance use disorders did not differ with respect to gender. Conclusions Despite a large gap between probable population prevalence of gambling disorder and the number of treated patients, the number of patients treated in out-patient health care with a gambling disorder diagnosis increased over time, with an increasing treatment uptake in younger individuals. Psychiatric comorbidity is common in gambling disorder patients in the health care system, with a higher prevalence in women.